Aggressive Fibromatosis in a postpartum woman: A Case Report - Goutham, V.V.N.; Vandana, Mrudula; Songa, Ramya (International Journal of Psychosocial Rehabilitation, 2020)
-Desmoid-type fibromatosis often emerges from the rectus abdominis muscle in postpartum females and in scars because of the abdominal procedure, they will moreover additionally rise up in any skeletal muscle. Desmoid tumors generally have a tendency to infiltrate adjacent muscle bundles, often entrapping them and causing their degeneration. They may moreover be derived from mesenchymal stem cells. Despite the fact that fixation to musculoaponeurotic systems is apparent, the overlying skin could be normal. We document a 46 yr old woman patient with a desmoid tumor of the anterior abdominal wall, beneath the umbilicus, who underwent partial excision together with abdominal repair. The affected person had a history of hysterectomy 10 years back. The preoperative assessment covered abdominal ultrasound, computed tomography, and magnetic resonance imaging. The histology confirmed a desmoid tumor.